Mild traumatic brain injury characteristics do not negatively influence cognitive processing therapy attendance or outcomes. (September 2019) - Crocker, Laura D.; Jurick, Sarah M.; Thomas, Kelsey R.; Keller, Amber V.; Sanderson-Cimino, Mark; Hoffman, Samantha N.; Boyd, Briana; Rodgers, Carie; Norman, Sonya B.; Lang, Ariel J.; Twamley, Elizabeth W.; Jak, Amy J.
Abstract: Some providers have expressed hesitation about the appropriateness of PTSD treatment for veterans with a history of mild traumatic brain injury (mTBI), given concerns that TBI-related sequelae may negatively affect PTSD treatment and/or should be the focus of treatment instead. However, research suggests that those with a history of mTBI can benefit from evidence-based PTSD treatment. To extend these findings, we examined whether specific mTBI injury markers were associated with PTSD treatment attendance and response. Iraq/Afghanistan-era veterans with PTSD and history of mTBI (N = 88) all received Cognitive Processing Therapy (CPT; either standard CPT without the trauma account or SMART-CPT, a modified version of CPT that included cognitive rehabilitation strategies). Analyses examined whether time since injury, presence of loss of consciousness (LOC) or posttraumatic amnesia (PTA), and number and mechanism of mTBIs were associated with treatment attendance or response. None of the five injury variables examined were associated with number of treatment sessions attended. Multilevel modeling indicated that injury variables did not moderate treatment response (across treatment conditions) in terms of change in PTSD and depression symptoms. There was a three-way interaction showing that individuals who denied ever experiencing LOC exhibited a greater decrease in PTSD and depression symptoms in standard CPT relative to those in the SMART-CPT. Thus, a history of mTBI should not preclude individuals from receiving standard CPT, regardless of injury characteristics. In fact, PTSD treatment should often be a first line of treatment for these veterans, given evidence of a mental health etiology to persistent post-concussive symptoms.